Development and kinematic analysis of robotic orthoses - Teng, Liek Yek. (2009)
Recent advances in robotic technology have led to the development of powered orthotic devices which can be used as rehabilitation aids. Robotic orthoses showed contribution in improving walking in patients with spinal cord injury. The purpose of these machines is to replace therapist manual assistance, increase the amount of stepping practice while decreasing therapist effort.